Perancangan dan Pembuatan Simulator Kompresor Torak Kapasitas 3 Bar Sekala Laboratorium - Andre Rizky; Gunawan Hidayat; Muhammad Haris Ali Murfi; Sulis Yulianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to design and build a laboratory-scale 3-bar reciprocating compressor simulator as a learning tool to understand the working principles of a single-cylinder reciprocating compressor. The design process includes material selection, frame construction, component installation, and piping system, as well as structural analysis using SolidWorks. Tests were conducted to measure mass flow rate, flow velocity, and pressure distribution. The results showed that increasing valve opening and motor speed increased the flow rate and mass flow rate, with the highest value being 0.0000338 kg/s at 1480 rpm. The piping system was capable of delivering pressurized air up to 3 bar, with even heat distribution and a peak temperature of 32°C. The structural analysis results showed agreement between theoretical calculations and simulations with a deviation below 15%. The strength of the welded joints had a safety factor of 182.8, indicating the frame could safely withstand operational loads. This simulator is considered effective as an interactive learning tool to support theoretical and practical understanding in mechanical engineering.